Neurobiology of Depression and Anxiety in Parkinson's Disease - Osamu Kano; Ken Ikeda; Derek Cridebring; Takanori Takazawa; Yasuhiro Yoshii; Yasuo Iwasaki (Parkinson's Disease)
Depression and anxiety are common in Parkinson's disease (PD) and have important consequences on quality of life. These have long been recognized as frequent accompanying syndromes of PD, and several reports suggest that these are the causative process or risk factors that are present many years before the appearance of motor symptoms. The neurochemical changes in PD involving dopamine, norepinephrine, and serotonin might be related to the pathophysiology of depression and anxiety, but this is still not clear. Several studies showed that anxiety in PD patients occurs earlier than depression, during premotor phase, suggesting that there may be a link between the mechanisms that cause anxiety and PD. Whereas a recent study reported that PD patients with depression and anxiety were associated with different demographic and clinical features.